Flow Model Selection for Water Soluble Polymer Solutions - Muhanned A.R. Mohammed (مجلة النهرين للعلوم الهندسية, 2009)
This research deals with the effect of type and concentration of different polymer solutions on rheological behavior and apparent viscosity. All polymers studied in this work are water soluble, which are: XC-polymer, Carboxymethyl cellulose (two types), Hydroxyethyl cellulose and Polyvinyl alcohol. 55 experiments were